X+1/3=10-x+2/2

Simple and best practice solution for X+1/3=10-x+2/2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for X+1/3=10-x+2/2 equation:



X+1/3=10-X+2/2
We move all terms to the left:
X+1/3-(10-X+2/2)=0
We add all the numbers together, and all the variables
X-(-1X+11)+1/3=0
We get rid of parentheses
X+1X-11+1/3=0
We multiply all the terms by the denominator
X*3+1X*3+1-11*3=0
We add all the numbers together, and all the variables
X*3+1X*3-32=0
Wy multiply elements
3X+3X-32=0
We add all the numbers together, and all the variables
6X-32=0
We move all terms containing X to the left, all other terms to the right
6X=32
X=32/6
X=5+1/3

See similar equations:

| X+4/18=7/9+x-6/3 | | P=6400x-18x^-400 | | 33=8+8y | | 7/5(2-x)-5/2(x+12)=8/3(1-7x) | | 11x+4=27 | | F(1)=3x^2-5x+6 | | F(0)=3x^2-5x+6 | | 3(-9x-21)+11=8(x-1)-4 | | F(x)=3x²-5x+6 | | 3(2a-2)=3a-3 | | 3*a=4 | | 3/5×=24x | | 5x2=2x+6 | | 10000+5000*x=500*2^x | | −2x+2=  x−13 | | −2x+2=  x−13x−13 | | 63+3m=8 | | 3+3=-3(6x-2) | | 3(2x+5)=-11+8 | | 4(9+3x)=6(2x+6) | | A-2x=3B | | 4m-5+3m=7m-6 | | x-20=5(7-4) | | 2(x-3)=14-3/5 | | h/3=-16 | | 1/7b+5=15 | | X/32+x=22 | | 2∣x−1∣+3=13 | | 2|x-1|+3=13 | | 2=-9n+23-n | | (9m+4)^2=0 | | 5x-2-2x=3x-7 |

Equations solver categories